Containerization Approach for Secure Internet of Medical Things (IoMT) Communication Protocols - OYEDEMI, OLUYEMISI; Zegarra Rodriguez, Demostenes; Lopes Rosa, Renata; Ugochukwu, Okwudili Mathew (INFOCOMP Journal of Computer Science, 2025)
The need for secure communication protocol has become very paramount due to the rapid growth of IoMT devices. Lack of robust security measure for communication protocol in IoMT environment renders them vulnerable to cyber-attacks. Secure communication protocols also address a major aspect of IoT security. This paper presents containerization-based framework as an approach that can be deployed, managed, and orchestrated on various IoMT devices and platforms for securing communication protocols. Containerization of communication protocol involves packaging communication protocols into containers. This approach provides a lightweight, portable, and secure way to deploy and manage communication protocols. Containerizing the communication protocols can be executed efficiently, reliably, securely without compromising the integrity and functionality of devices. By implementing robust and secure communication protocol, IoT environment can be better equipped to defend against potential cyber threats. Keywords: Internet of Medical Things (IoMT), Containerisation, Security, Communication Protocol